2010
DOI: 10.1093/nar/gkq850
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of somatic cell reprogramming through inducible mir-302 expression

Abstract: Global demethylation is required for early zygote development to establish stem cell pluripotency, yet our findings reiterate this epigenetic reprogramming event in somatic cells through ectopic introduction of mir-302 function. Here, we report that induced mir-302 expression beyond 1.3-fold of the concentration in human embryonic stem (hES) H1 and H9 cells led to reprogramming of human hair follicle cells (hHFCs) to induced pluripotent stem (iPS) cells. This reprogramming mechanism functioned through mir-302-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
296
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(307 citation statements)
references
References 21 publications
6
296
1
4
Order By: Relevance
“…Previous studies showed that key transcription regulators such as Oct4, Sox2, and Nanog occupy the promoters of a set of miRNA genes (e.g., the miR-290 cluster and miR-302/367 cluster). These miRNAs not only play important roles in the maintenance of ES cell pluripotency and self-renewal but also promote iPSC generation by suppressing the expression of their specific target genes [24,[27][28][29], suggesting that the direct regulation of miRNA expression is one important way for the defined factors to specifically regulate gene expression and cell reprogramming. In the present study, we found that the defined factor Sox2 binds to the promoter region of miR-29b and regulates the transcription of endogenous miR-29b during iPSC induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that key transcription regulators such as Oct4, Sox2, and Nanog occupy the promoters of a set of miRNA genes (e.g., the miR-290 cluster and miR-302/367 cluster). These miRNAs not only play important roles in the maintenance of ES cell pluripotency and self-renewal but also promote iPSC generation by suppressing the expression of their specific target genes [24,[27][28][29], suggesting that the direct regulation of miRNA expression is one important way for the defined factors to specifically regulate gene expression and cell reprogramming. In the present study, we found that the defined factor Sox2 binds to the promoter region of miR-29b and regulates the transcription of endogenous miR-29b during iPSC induction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ectopic expression of the miR-302/367 cluster together with the knockdown of HDAC2 was shown to efficiently reprogram mouse and human somatic cells into iPSCs without requiring exogenous transcription factors [25], and a combination of mature miRNAs (miR-200c, miR-302s, and miR-369s) can also reprogram mouse and human cells into the pluripotent state [26]. Recent studies have revealed that both Oct4 and Sox2 are involved in the regulation of miR-302 expression in hESCs [27,28]; moreover, stimulating miR-302 expression in somatic cell reprogramming causes DNMT1 deficiency and global DNA hypomethylation [29]. These results indicate that miRNAs may serve as important mediators and play major roles in epigenetic and gene expression remodeling during OSKM-triggered iPSC generation.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, this variability is not random, but only occurs at certain genes or MiR367 expression activates Oct4 gene expression and suppresses Hdac2. Moreover, miR-302-targeted co-suppression of four epigenetic regulators, AOF2 (KDM1/LSD1), AOF1, MECP1-p66, and MECP2, could cause global DNA demethylation (Lin et al, 2011). The second study directly transfected mature miRNAs with a combination of miR-200c, miR-302s, and miR-369s family miRNAs.…”
Section: Ipsc and Esc Differencesmentioning
confidence: 99%
“…These discrepancies could be caused by different delivering systems. For example, it was found that miR-302-induced reprogramming is dosage dependent (Lin et al, 2011), so the microRNA concentration must be within a specifi c range.…”
Section: Ipsc and Esc Differencesmentioning
confidence: 99%
“…Therefore, miR-302 could also be applied to enhance the reprogramming efficiency of somatic cells to iPS cells. With induced miR-302 expression beyond 1.3-fold of the concentration in hES cells, Lin et al [85] reprogrammed human hair follicle (hHF) cells to iPS cells. The expression of the miR-302 significantly decreased the epigenetic regulators AOF2, DNMT1 and MECP1/2, leading to global genomic DNA methylation and histone modifications.…”
Section: Micro Rnasmentioning
confidence: 99%